Understanding the linewidth of a quantum cascade laser - Leow, Amy Min Huay (2017)
Quantum Cascade (QC) lasers are semiconductor injection lasers transmitting in the mid-infrared to the terahertz of the electromagnetic spectrum. QC laser is operated based on the intersubband transitions in a many alternating layers of semiconductor material compositions. This forms a many quantum-well heterostructure. There are several advantages of applying intersubband transition.